2010
DOI: 10.4102/koedoe.v52i1.879
|View full text |Cite
|
Sign up to set email alerts
|

The socio-economic impact of Africa’s oldest marine park

Abstract: South African National Parks (SANParks) plays a major role in the tourism industry and has three primary functions, namely to conserve biodiversity, to create tourism and recreational opportunities and to build strong community relations. These parks, therefore, have a definite socio-economic impact on adjacent communities, although little is known about this impact. The main aim of this study was to determine the socio-economic impact of Africa’s oldest marine park, namely Tsitsikamma National Park, which for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Tourism has significant potential as an MPA financing mechanism [15,[64][65][66] and may lead to economic benefits at a broader scale; however, the level of local community benefit from and involvement in tourism can be minimal. Some MPAs, such as the Great Barrier Reef MPA in Australia [67], Mendes Island MPA in the Mediterranean [68], and Tsitskamma National Park in South Africa [69], have resulted in significant increases in tourism visitation and revenue [51,70]. A global study of 78 coral reef MPAs found that 75% of tourism jobs were retained locally [71].…”
Section: Livelihood and Community Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Tourism has significant potential as an MPA financing mechanism [15,[64][65][66] and may lead to economic benefits at a broader scale; however, the level of local community benefit from and involvement in tourism can be minimal. Some MPAs, such as the Great Barrier Reef MPA in Australia [67], Mendes Island MPA in the Mediterranean [68], and Tsitskamma National Park in South Africa [69], have resulted in significant increases in tourism visitation and revenue [51,70]. A global study of 78 coral reef MPAs found that 75% of tourism jobs were retained locally [71].…”
Section: Livelihood and Community Outcomesmentioning
confidence: 99%
“…Ecological services, such as coastal protection, may also lead to reduced vulnerability and improved household security. Yet MPAs and related developments can also lead to contrary socio-economic outcomes, including increased conflict and political struggle, exacerbated vulnerabilities, negative sociocultural change, increased restrictions, decreased levels of power and alienation in natural resource management processes, forced migration, loss of assets, increased social tension, loss of social and educational facilities, inequitable distribution of benefits, further marginalization of marginalized groups, loss of tenure, as well as decreased food security in the short term and for some groups [10,16,41,43,50,53,54,65,69,[72][73][74][75]88,89,91,93,[95][96][97][98][99][100]. In short, livelihood and socio-economic outcomes from MPAs vary widely and can range from very positive to very negative depending on the context and inputs.…”
Section: Livelihood and Community Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research methodology was based mostly on measuring the visitors' spending within the park and qualitative surveys among local residents and entrepreneurs (Oberholzer et al 2010;Saayman, Saayman 2006). Any comprehensive assessment also requires data to be obtained from national parks' managing bodies, as well as secondary data from public statistics.…”
Section: Economic Impact Of Protected Areasmentioning
confidence: 99%